Uso de bebidas vegetales de Chocho (Lupinus mutabilis), Garbanzo (Cicer arietinum) y Amaranto (Amaranthus) como sustitución de la leche de vaca en yogurt. - Cerna Mora, María José (2024)
In the search for healthy and nutritious alternatives to milk, plant-based beverages are becoming increasingly popular. Made from ingredients such as chickpeas, chocho, and amaranth, these beverages have been the subject of several studies due to the growing demand for natural and nutritious options from lactose intolerant people. This literature review study found amaranth to be the vegetable beverage with the most outstanding nutritional profile, with a protein content of 38.9%, 8% fiber, 70% carbohydrate, 0.4% potassium and 0.25% magnesium. This makes it an excellent source of slow-release energy, ideal for vegetarians and vegans. Analysis of the yogurt production process based on these drinks shows that the chickpea drink is the most suitable in terms of time, efficiency and cost reduction. It eliminates the need for soaking, grinding and initial filtering, significantly reducing production time and cost. In addition, the bacterial fermentation of lactic acid improves the nutritional and functional value of the final beverage. The purpose of this work is to provide solid knowledge of the nutritional profile of 3 natural beverages to be implemented in the elaboration of yogurt, taking into account the elaboration process to be applied to obtain better results, and to provide healthy alternatives to lactose intolerant people and people who want to lead a balanced life.